Temperate Forest Floors: Ecosystem Hubs in Transition? - Friederike Lang; Jörg Prietzel; Frank Hagedorn; Klaus Kaiser; Stefanie Schulz; Mathias Mayer; Lars Vesterdal; Jürgen Bauhus; Maï Bergmann; Sebastian Bibinger; Martin I. Bidartondo; Jingxuan Olivia Chen; et al. (Global Change Biology, 2026)
The forest floor (FF) plays a key role in carbon, nutrient, and water cycling. It is the biologically most active compartment of forest soils, highly responsive to environmental conditions. Yet, its response to current changes in environmental conditions and forest management is understudied. Temperate forests are among the best studied ecosystems globally, providing the necessary ecological and biogeochemical background information to assess FF changes. Here, we focus on identifying existing knowledge and gaps in our understanding of the functioning of the FF. Interactions between FF biota and abiotic FF components show multifactorial dependencies with environmental conditions and drive FF turnover. Vice versa, the turnover of FF regulates carbon, nutrient, and water cycling. With slow litter decomposition and limited bioturbation, organic matter accumulates, nutrients cycle tightly within the FF, and water passes through this layer partly along preferential pathways. With rapid litter decomposition and intense bioturbation, FF accumulation is little, the mineral soil is the main nexus for plant nutrient uptake and organic matter transformation, and water infiltrates the mineral soil more homogeneously. The interconnectedness with the adjacent ecosystem compartments is a crucial feature of the FF, feeding back to its functioning and making it a central hub of forest processes. The FF morphology reflects these processes and therefore has untapped potential as an indicator of soil and ecosystem health. Under forest change, the FF might lose its functionality, with negative impacts on nutrient provision, water storage, and carbon sequestration. Consequences for forest growth could be strong and even detrimental. Hence, improved knowledge of FF characteristics and their linkages to mineral soils and aboveground ecosystem compartments is crucial for assessing forest resilience to progressing environmental changes.

Three perspectives on the prediction of chemical effects in ecosystems - Anke Schneeweiss; Noël P. D. Juvigny‐Khenafou; Stephen Osakpolor; Andreas Scharmüller; Sebastian Scheu; Verena C. Schreiner; Roman Ashauer; Beate I. Escher; Florian Leese; Ralf B. Schäfer (Global Change Biology, 2023)
The increasing production, use and emission of synthetic chemicals into the environment represents a major driver of global change. The large number of synthetic chemicals, limited knowledge on exposure patterns and effects in organisms and their interaction with other global change drivers hamper the prediction of effects in ecosystems. However, recent advances in biomolecular and computational methods are promising to improve our capacity for prediction. We delineate three idealised perspectives for the prediction of chemical effects: the suborganismal, organismal and ecological perspective, which are currently largely separated. Each of the outlined perspectives includes essential and complementary theories and tools for prediction but captures only part of the phenomenon of chemical effects. Links between the perspectives may foster predictive modelling of chemical effects in ecosystems and extrapolation between species. A major challenge for the linkage is the lack of data sets simultaneously covering different levels of biological organisation (here referred to as biological levels) as well as varying temporal and spatial scales. Synthesising the three perspectives, some central aspects and associated types of data seem particularly necessary to improve prediction. First, suborganism‐ and organism‐level responses to chemicals need to be recorded and tested for relationships with chemical groups and organism traits. Second, metrics that are measurable at many biological levels, such as energy, need to be scrutinised for their potential to integrate across levels. Third, experimental data on the simultaneous response over multiple biological levels and spatiotemporal scales are required. These could be collected in nested and interconnected micro‐ and mesocosm experiments. Lastly, prioritisation of processes involved in the prediction framework needs to find a balance between simplification and capturing the essential complexity of a system. For example, in some cases, eco‐evolutionary dynamics and interactions may need stronger consideration. Prediction needs to move from a static to a real‐world eco‐evolutionary view.

Diversity of soluble salt concentrations on volcanic ash aggregates from a variety of eruption types and deposits - Mathieu Colombier; Sebastian B. Mueller; Ulrich Kueppers; Bettina Scheu; Pierre Delmelle; Corrado Cimarelli; Shane J. Cronin; Richard J. Brown; Manuela Tost; Donald B. Dingwell (Bulletin of Volcanology, 2019)

Drivers of nitrogen leaching from organic layers in Central European beech forests - Martin T. Schwarz; Sebastian Bischoff; Stefan Blaser; Steffen Boch; Fabrice Grassein; Bernhard Klarner; Barbara Schmitt; Emily F. Solly; Christian Ammer; Beate Michalzik; Peter Schall; Stefan Scheu; et al. (Plant and Soil, 2016)

A comparison of the strength of biodiversity effects across multiple functions - Eric Allan; Wolfgang W. Weisser; Markus Fischer; Ernst-Detlef Schulze; Alexandra Weigelt; Christiane Roscher; Jussi Baade; Romain L. Barnard; Holger Beßler; Nina Buchmann; Anne Ebeling; Nico Eisenhauer; et al. (Oecologia, 2013)

Functionally and phylogenetically diverse plant communities key to soil biota - Alexandru Milcu; Eric Allan; Christiane Roscher; Tania Jenkins; Sebastian T. Meyer; Dan Flynn; Holger Bessler; François Buscot; Christof Engels; Marlén Gubsch; Stephan König; Annett Lipowsky; et al. (Ecology, 2013)
Recent studies assessing the role of biological diversity for ecosystem functioning indicate that the diversity of functional traits and the evolutionary history of species in a community, not the number of taxonomic units, ultimately drives the biodiversity–ecosystem‐function relationship. Here, we simultaneously assessed the importance of plant functional trait and phylogenetic diversity as predictors of major trophic groups of soil biota (abundance and diversity), six years from the onset of a grassland biodiversity experiment. Plant functional and phylogenetic diversity were generally better predictors of soil biota than the traditionally used species or functional group richness. Functional diversity was a reliable predictor for most biota, with the exception of soil microorganisms, which were better predicted by phylogenetic diversity. These results provide empirical support for the idea that the diversity of plant functional traits and the diversity of evolutionary lineages in a community are important for maintaining higher abundances and diversity of soil communities.

Permeability and degassing of dome lavas undergoing rapid decompression: An experimental determination - Sebastian Mueller; Oleg Melnik; Oliver Spieler; Bettina Scheu; Donald B. Dingwell (Bulletin of Volcanology, 2005)